(untitled) (Sebha University Conference Proceedings, 2024)
Leukaemia is a group of malignant neoplasms that arise from altered hematopoietic cells, leading to a diverse range of complex and heterogeneous diseases. Acquired chromosomal aberrations, including deletions, translocations, and amplifications, contribute to the emergence of various subtypes of leukaemia. As a result, karyotyping has become a crucial tool for diagnosing and classifying different forms of leukaemia. This study utilized the chromosomal G-banding method, a cross-sectional approach, to examine the karyotype of peripheral blood samples from five Libyan patients with leukaemia at the Benghazi Pediatric Hospital. The analysis successfully revealed several chromosomal abnormalities, and the patients were classified into the subclasses of B-ALL and AML leukaemia disorders. These findings highlight the significance of karyotyping in diagnosing and predicting leukaemia. Furthermore, this research illustrated how precise karyotyping analysis can provide invaluable information that can ultimately improve patient outcomes and treatment strategies.